The Use of Blended Teaching in Higher Medical Education during the Pandemic Era - Xue-Tao Fu; Yi Hu; Bing-Chun Yan; Yun-Gen Jiao; Shi-Jun Zheng; Ying-Ge Wang; Jiang-Yun Zhang; Zheng-Bing Wang (International Journal of Clinical Practice)
Objective. This study aims to compare the effect of blended teaching and traditional teaching in higher medical education during the pandemic era. Methods. Taking the teaching of neurology as an example, 293 Yangzhou University Clinical Medicine 2016 undergraduate students were selected as the research subjects, and were randomly divided into 2 groups a blended teaching group (n = 148) and a traditional teaching group (n = 145), and received blended teaching and traditional teaching, respectively. The blended teaching was based on a Massive Open Online Course, problem-based learning, and case-based learning and supplemented by Tencent video conferences, QQ messaging groups, and other auxiliary teaching tools. At the end of the course, the teaching effect and satisfaction rate were evaluated through theory assessment, practical skills assessment, and an anonymous questionnaire survey. Results. There were significant differences in theoretical achievements (81.83 ± 6.23 vs 76.79 ± 6.87, P<0.001) and practical skill achievements (84.74 ± 6.50 vs 78.48 ± 6.53, P<0.001). In addition, significant differences in all aspects of satisfaction rate were observed between the two groups (all P<0.001). Conclusion. Blended teaching is beneficial to students’ learning and stimulates their enthusiasm, cultivates clinical thinking ability, and improves teaching quality. Thus, it has played a positive role in the reform of higher medical teaching during the pandemic era.